Simulation Analysis of Iron Roughneck's Stretching Device based on MATLAB and Adams. Issue 1 (January 2021) - Li, Quan; Sha, Yongbai; Zhao, Xiaoying; Piao, Chong
Abstract: In this paper the composition and working principle of stretching device for arm iron roughneck are introduced, and the kinematic model of the mechanism is established. The kinematic parameter curves of each necessary component are got by using complex vector method and solving the model with MATLAB. The kinematics simulation analysis of the virtual prototype of the iron roughneck's stretching device is carried out by Adams, and then the kinematic parameter curves of each component are obtained, and compared with the curve obtained by MATLAB. The results show that the performance of iron roughneck stretching device is good. Most of the parameter curves calculated by MATLAB are consistent with the results of Adams simulation, and the influencing factors of the curve inconsistency are analyzed.